Hypomonē (ὑπομονη) - Hypomenō (ὑπομένω) dalam Surat kepada Orang Ibrani dan Relevansinya bagi Umat Katolik di Masa Pandemi - Franciscus Diky Palmana (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
The starting point of this essay is the fact of human suffering which resulted from the Covid-19 pandemic, where the faithful attempt to persevere in managing life both in the Church and the society. The paper attempts to find inspiration from The Epistle to the Hebrews that consoles the believers in the time of persecution. Its author uses the word Hypomonē (perseverance) to address the readers in Emperor Nero's time who were suffering for their belief in Christ. The Epistle uses an educational tradition to highlight perseverance known in both Hebrew and Greek societies. The text invites readers to persevere in this suffering like an athlete who must train in face of competition, and like a child who is educated in discipline and love by his father.